The Long Journey of Islamic Civilization: Traces of Its Triumphs and Setbacks - Zakiyatun Nufus; Maftuh Sujana; Dinda Ayu; Putri Nurhaliza (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This article about the long journey of Islamic civilization, tracing its glory to the top position and its decline to the next period. Islamic civilization played an important role in the development of global knowledge, culture, politics, and economics especially during the Golden Age during the reigns of great caliphs such as the Umayyad, Abbasid and Andalusian dynasties. This article reviews the various internal and external factors involved in the establishment of the dynasty, including the intellectual contributions of Muslim scholars and a stable system of government. Instead, this article also discusses the causes of the decline of Islamic civilization, such as internal conflicts, intellectual stagnation, and colonialism. Through the approach of a story fund, this article aims to provide an understanding of the dynamics that shaped the course of Islamic civilization, as well as lessons that can be taken for potential revival in the current era. This study employs a historical-analytical approach by examining classical and contemporary sources to capture the continuity and transformation of Islamic civilization over time. The discussion highlights how religious values, scientific inquiry, and cultural openness became key drivers of civilizational progress. Furthermore, the article emphasizes the interaction between Islamic civilization and other civilizations, which contributed to mutual knowledge exchange and global development. By analyzing past successes and failures, this article underscores the relevance of Islamic civilization in addressing modern challenges.